Knowledge and Attitudes of Students About Water Pipe Smoking at Technical Institute / Alsuwayra in Middle Technical University - Ahmed K. Jawad; Jasim A. Khaleefah; Ammar A. Okab (Journal of Techniques)
Water pipe (WP) is also referred to as Narghile, Hubble-bubble, Ghoza, and Hookah, depending on the country. Water pipe tobacco smoking is a type of tobacco consumption that involves smoking flavored or unflavored tobacco via a single or multi-stemmed instrument. The objective of the study knowledge and attitudes about water pipe (shisha) smoking. A descriptive cross-sectional study design (mixed methods design) was carried out at the technical institute –Suwaira. Included (240) students. The sampling technique was a random sample, and data was collected using an interview with students, from December 2021 to March 2022. Results of the study show demographic characteristics of students' age groups (21-24) years (50.0%), type of smoking (21.2%) of smoking both (cigarettes and water pipes), the overall level of knowledge to study sample about waterpipe smoking was intermediate knowledge (67.1%). The conclusions of the study show a majority of participants were smoking (52.1%), and most of them were smoking both (Cigarettes, Water pipes). Knowledge of students about waterpipe smoking was more (Yes) responses are harmful to health, the overall level of knowledge about waterpipe smoking was intermediate and poor knowledge. The study recommends great interest to the Ministry of Health and the consideration of the adjustment of strategies to improve knowledge, change attitudes, and correct the misconceptions about the habit of WPS, especially among students in colleges and universities.